Analisa Penataan Ruang Pada Pasar Raya I Salatiga - Masayu, Murista Mutiara; Rukayah , R. Siti (Nature : National Academic Journal of Architecture, 2025)
A traditional market is a place where traders and buyers gather, characterized by direct transactions between them. Traditional markets typically consist of stalls or outlets, los (permanent or semi-permanent trading spaces), and open areas. One city that still heavily relies on markets for its economy is Salatiga. Pasar Raya I Salatiga is one of the largest markets in the city, comprising 69 shop houses, 240 stalls, and 2,150 los. However, the number of these facilities is not proportional to the number of traders currently operating there. One contributing factor is the suboptimal utilization of planned spaces. Initial observations at Pasar Raya I Salatiga reveal the presence of underutilized areas (commonly referred to as "dead spots"), which are marginal or vacant zones within the building. Due to inefficient spatial layout and circulation, these areas receive less foot traffic and attention. This study aims to determine whether the current spatial arrangement and circulation in Pasar Raya I Salatiga contribute to the formation of such underutilized spaces. A descriptive qualitative method was employed, analyzing data collected through field observations, questionnaires, and literature review. Behavioral mapping techniques, including place-centered and person-centered mapping, were used. The findings indicate that the existing spatial arrangement and circulation patterns at Pasar Raya I Salatiga are indeed significant factors contributing to the emergence of underutilized spaces (dead spots).